2004
DOI: 10.1097/00124784-200401000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interdisciplinary Rounds on Length of Stay in a Telemetry Unit

Abstract: IRs did not decrease LOS in a telemetry ward. Whereas a potential benefit of IRs in other settings cannot be ruled out, this study emphasizes the importance of rigorous testing of strategies to enhance the quality or reduce the costs of inpatient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 8 publications
0
31
1
Order By: Relevance
“…11 A third, smaller study showed no effect on LOS and cost with the use of IDR. 14 In light of the final sample size for the intervention unit being slightly less than our intended target, it is possible that our study was underpowered to detect a difference in LOS or cost. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…11 A third, smaller study showed no effect on LOS and cost with the use of IDR. 14 In light of the final sample size for the intervention unit being slightly less than our intended target, it is possible that our study was underpowered to detect a difference in LOS or cost. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 95%
“…Although two studies documented a reduction in LOS and cost with the use of IDR, 11,13 another study showed no effect. 14 This study had three aims. The first was to assess the impact of an intervention, structured inter-disciplinary rounds (SIDR), on both physicians' and nurses' ratings of collaboration and teamwork and safety climate.…”
Section: Introductionmentioning
confidence: 99%
“…13 A third, smaller study found no effect on LOS and cost with the use of IDR. 15 No prior study has evaluated the effect of IDR on LOS and cost in a nonteaching hospitalist service setting.…”
Section: Discussionmentioning
confidence: 99%
“…12,14 Previous studies also indicate variable effects of IDR on length of stay (LOS) and cost with 2 studies finding a reduction in LOS and cost with the use of IDR, 12,13 while another did not. 15 Furthermore, all these prior studies evaluated the use of IDR on resident-covered teaching services. The effect IDR has on collaboration, LOS, and cost in a nonteaching hospitalist service setting is not known.…”
mentioning
confidence: 99%
“…7,8 Interdisciplinary rounds (IDR), also known as multidisciplinary rounds, provide a means to assemble hospital care team members and improve collaboration. [9][10][11][12][13] Prior research on the use of IDR has demonstrated improved ratings of collaboration, 11,12 but inconsistent effects on length of stay and cost. 10,12,13 Notably, the format, frequency, and duration of IDR in prior studies has been variable and no studies, to our knowledge, have evaluated teamwork performance during IDR.…”
Section: Discussionmentioning
confidence: 99%